Child Maltreatment, Youth Violence, Intimate Partner Violence, and Elder Mistreatment: A Review and Theoretical Analysis of Research on Violence Across the Life Course. (January 2022) - Herrenkohl, Todd I.; Fedina, Lisa; Roberto, Karen A.; Raquet, Kira L.; Hu, Rita X.; Rousson, Ashley N.; Mason, W. Alex
This article reports the results of a scoping review of the literature on life-course patterns of violence that span the developmental periods of childhood, adolescence, and early and middle adulthood. We also assess the evidence on elder mistreatment and its relation to earlier forms of violence. Additionally, we draw on theories and empirical studies to help explain the transmission of violence over time and relational contexts and the factors that appear to mitigate risks and promote resilience in individuals exposed to violence. Results suggest that encounters with violence beginning in childhood elevate the risk for violence in subsequent developmental periods. The strongest connections are between child maltreatment (physical abuse, emotional abuse, sexual abuse, and neglect) and violence in adolescence and between violence in adolescence and violence in early and middle adulthood. Persistence of violence into older adulthood leading to elder mistreatment is less well-documented, but probable, based on available research. We conclude that more attention should be paid to studying developmental patterns and intersecting forms of violence that extend into old age. To eradicate violence in all its forms, considerably more must be done to increase awareness of the repetition of violence; to connect research to actionable steps for prevention and intervention across the life course; and to better integrate systems that serve vulnerable children, youth, and adults. Primary prevention is essential to breaking the cycle of violence within families and to alleviating the risks to children caused by poverty and other external factors such as social disconnection within communities.